Should high‐dose N‐acetylcysteine be given in cases of massive paracetamol overdoses: A narrative review - Erichsen, Philip Ahle; Dalhoff, Kim; Andersen, Michael Asger (Basic & clinical pharmacology & toxicology, 2024)
N‐acetylcysteine (NAC) is regarded as an effective treatment of paracetamol overdoses. However, in cases of “massive” paracetamol overdoses, recent studies indicate that patients may not be sufficiently treated with the standard dose of NAC (300 mg/kg over 20–21 h). The subject is further complicated because “massive overdoses” and “high‐risk” are defined differently; some studies use the ingested amount (e.g., >40 g), and some studies use blood concentrations of paracetamol and transaminases. This narrative review investigates whether high‐dose NAC significantly decreases the risk of hepatotoxicity in patients with massive paracetamol overdoses. Three observational studies were analysed; one study with 373 patients found no significant difference (odds ratio [OR]: 1.27, 95% confidence interval [CI]: 0.49–3.29). One study with 79 patients found a significant difference (OR: 0.27, 95% CI: 0.08–0.94). The third study with 89 patients found a significant difference in hepatoxicity between the groups (p = 0.043). There are no solid evidence to support that treatment with high‐dose NAC significantly reduces the rate of hepatotoxicity in patients presenting with massive paracetamol overdoses. Differences in inclusion criteria in the included studies make the studies incomparable. This paper shows that standardized inclusion is needed to determine whether a high‐dose NAC regimen should be included in clinical practice.